(untitled) (One Health Journal of Nepal, 2022)
It is reported that about 1 in 11 adults have diabetes mellitus (DM) globally. A total of 415 million people have DM and an estimated 193 million people have undiagnosed DM worldwide. Where, type 2 diabetes mellitus (T2DM) accounts for around 90% of patients with DM. Yoga interventions appeared to be more effective in T2DM as compared to physical exercise interventions which may be because of various aspects of yoga other than the physical one. The yoga intervention involves subtle components such as mindfulness, relaxation, breath regulation, and notional corrections. The mechanism through which yoga works may be the down-regulation of the sympathetic nervous system and the hypothalamic-pituitary-adrenal axis which may lead to the improvement in psychological health, quality of sleep, autonomic balance, and reduction in insulin resistance. Lifestyle modification programs such as yoga interventions on a regular basis for long duration have potential to manage and cure T2DM. The government and the concerned bodies should pay attention to this area.